Aplicação do método da eletrorresistividade na investigação de plumas de contaminação em aterros sanitários - Galdeano, Larissa Ruas [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The researching area of the Completion of Course Work is situated on the Old Sanitary Landfill of São Carlos city, which is located in Fazenda Guaporé. Besides its activities were already finished, there is a possibility of occurrence of a contaminants and slurry percolation produced by degradation of solid waste through a contamination plume. The objective of this research is consisted of an evaluation of lateral migration of a possible contamination plume at the environment by using geophysics methods. The method used on this research was the Geoeletric Method of Electrical Resistivity with the application of the Constant Separation Traversing (CST) technique with dipole-dipole array. This methodology allows the evaluation of materials resistivity values in subsurface by creating maps and sections and indicates possible contamination plumes percolations by the variability of the measured resistivities. There were made five investigation lines by using the Constant Separation Traversing Technique along the Sanitary Landfill, which were resulted on five pseudosections with measures of apparent resistivities and depths on the field that were posteriorly processed by the Res2dinv V. 3.5 software in order to create geoelectrical models with real values of resistivity. The integrated analysis of pseudosections and geoelectrical models of the five investigation lines in addition to the two Maps of Top Quota of Bedrock indicated that there are resistivity anomalies probably related to the percolation of a slurry contamination plume through fractures and faults of the bedrock and to the alteration soil and superficial sediment layers, which is recommended an physical and chemical investigation of those sites by accomplishing a probing drill or sampling

A área de estudo do Trabalho de Conclusão de Curso situa-se no Antigo Aterro Sanitário de São Carlos, localizado na Fazenda Guaporé. Apesar de suas atividades já terem sido finalizadas, existe a possibilidade de ainda ocorrer a percolação de contaminantes e de chorume produzidos pela degradação dos resíduos sólidos por meio de uma pluma de contaminação. O objetivo da pesquisa deste trabalho consistiu na avaliação da migração lateral de uma possível pluma de contaminação no meio físico por meio de métodos geofísicos. O método utilizado por este trabalho foi o Método Geoelétrico da Eletrorresistividade, com aplicação da Técnica do Caminhamento Elétrico (CE) com arranjo dipolo-dipolo. Esta metodologia permite avaliar os valores de resistividade dos materiais em subsuperfície através de seções e mapas e indicam possíveis percolações de plumas de contaminação pela variação das resistividades medidas. Neste estudo foram feitas cinco linhas de investigação pela técnica do Caminhamento Elétrico ao longo do Aterro Sanitário, na qual resultaram em cinco pseudo-seções com medidas obtidas em campo de resistividades e profundidades aparentes que foram posteriormente processadas pelo software Res2dinv V. 3.5 a fim de obter modelos geoelétricos com medidas reais de resistividade. A análise integrada das pseudo-seções e modelos geoelétricos das cinco linhas de investigação em conjunto com os Mapas da cota de topo da rocha sã indicou que as anomalias de resistividade estão provavelmente relacionadas a percolação da pluma de chorume por meio dos fraturamentos da rocha sã e dos horizontes de solo alterado da rocha são e sedimentos superficiais coluvionares, sendo recomendável uma análise físico-química por meio de perfuração de sondagem e amostragem nestes locais
Keywords: Geofisica; Aterro sanitário; Águas subterrâneas; Contaminação; Resíduos sólidos; São Carlos (SP)